1999
DOI: 10.1183/09031936.99.14232899
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the dose of inhaled flour: relation with nonspecific bronchial and immunological reactivities

Abstract: Because both bradykinin and tachykinins have a potent inflammatory action, these molecules may be involved in the late allergic response. The role of these molecules in airway microvascular permeability during the late allergic response in sensitized guinea-pigs was investigated.Three weeks after ovalbumin sensitization, the animals were pretreated with bradykinin B 2 receptor antagonist HOE 140, neurokinin 1 receptor antagonist CP 96,345 or vehicle, 30 min before the ovalbumin inhalation challenge. The occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Sometimes the ambient concentration is measured, but inhaled dose is seldom determined. The way to express results and the criteria of positivity are not as well defined as for the methacholine test [1][2][3][4]. However, a 20% (or 15%) fall in forced expiratory volume in one second (FEV1) is the criterion usually used to indicate a positive early reaction [1,[3][4][5].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Sometimes the ambient concentration is measured, but inhaled dose is seldom determined. The way to express results and the criteria of positivity are not as well defined as for the methacholine test [1][2][3][4]. However, a 20% (or 15%) fall in forced expiratory volume in one second (FEV1) is the criterion usually used to indicate a positive early reaction [1,[3][4][5].…”
mentioning
confidence: 99%
“…The way to express results and the criteria of positivity are not as well defined as for the methacholine test [1][2][3][4]. However, a 20% (or 15%) fall in forced expiratory volume in one second (FEV1) is the criterion usually used to indicate a positive early reaction [1,[3][4][5]. The current authors have demonstrated that the fall in FEV1 during the specific challenge can be compared to the distribution of the values of FEV1 during the control test with lactose [3].…”
mentioning
confidence: 99%
See 3 more Smart Citations